Impact of Language Barriers and Age on English Hearing Test App Accuracy for Polish Users - Małgorzata Pastucha; Elżbieta Gos; Henryk Skarżyński; W. Wiktor Jedrzejczak (OTO Open)
Abstract Objective The development of health applications (apps) includes those for testing hearing, although most of them are available only in English. This study investigates whether poor English language proficiency creates a barrier for Polish users in the accuracy of such an app in measuring self‐determined hearing thresholds. Study Design The study compared hearing thresholds measured by an English‐language app and a professionally conducted reference test, with attention to participants' English proficiency and age. Setting The English‐language app “Hearing test, Audiogram,” was used to determine hearing thresholds. A reference test was performed by an audiologist using specialized equipment. Methods Participants were 87 nonnative English language speakers aged 16 to 88. They were divided into 3 groups based on their proficiency in English: no knowledge (Group 1), basic (Group 2), and advanced (Group 3). The mean differences between hearing thresholds determined using the app and the reference tests were measured for each group. Results The accuracy of the results varied according to the level of English proficiency. A statistically significant difference was found between Group 1 (no knowledge) and Group 3 (advanced), with mean differences of 13.6, 9.3, and 6.7 dB for Groups 1, 2, and 3, respectively, meaning that discrepancies were larger in the less proficient groups. However, when participant age was considered, language proficiency was less important and was no longer a significant factor. Conclusion This study revealed that English language proficiency does affect the accuracy of mobile app‐based hearing tests, but age of the user is also important.